Borders of a Game: Analysis of the Practical Phenomenology and Other Trends of Nowadays - Voidogaitė, Viktorija (Vilnius University Open Series, 2020)
This article, through a prism of reduction, focuses on the gaming of practical phenomenology (M. van Manen), logical atomism (L. Wittgenstein), rhizomatic movement (Deleuze) as well as anthropocene moods in the playground of the education science. It also considers the practical manisfestatation of these fashionable philosophical methodologies and possible perspectives in the modern-day education. The text of the article joins the ideas of different methodologies to a critical gaming.
Keywords: practical phenomenology; reduction; language game